Study of air quality and noise levels in King Fahad International airport in Dammam, Saudi Arabia - Salama, Khaled Fikry; Obireed, Abdulrahman Al; Qarni, Abdulazziz Al; Bagawi, Mohammed Al; Namsha, Khaled Al (International Journal Of Community Medicine And Public Health, 2017)
Background: Air transportation growth has increased continuously over the years. Air quality and health impacts from aviation have been considered focusing mainly on the air pollutants emissions and noise exposure from aircraft landing/take-off, aircraft taxi/ servicing, local car traffic, fuel transportation and storage. This study aimed to assess noise pollution and air quality levels in King Fahad International Airport in Dammam. Methods:Measurements of noise levels and air quality parameters (Carbon monoxide (CO), Carbon Dioxide CO2, Ozone O3, Nitrogen Dioxide NO2, Sulphur Dioxide SO2, Volatile Organic Compounds VOCs and particulate matter PM10 were measured in taxiway, runway, cars parking area and waiting area using calibrated equipment. Results: the results of the present study revealed that airport workers are exposed to significant high levels of noise and different air pollutants parameters in different studied areas and airports activities. Conclusions:The situation in some of this area as taxiway, runway and cars parking calls for a rapid planning strategy for the control of airport. It may also be noted that the result of this study point to the need of further studies at the studied airport and others airports in Kingdom of Saudi Arabia as well.